LEARNING GEOGRAPHY WITH UNDERGROUND MAPS - GONZALEZ, Juan Antonio Garcia (European Journal of Geography, 2017)
Underground maps have become so popular and widespread that they have transcended the function for which they were created about a century ago. These maps fulfill faithfully the duty of guiding us across the metropolitan transport network. In addition, they have become iconic elements, merchandising and brand images of many of these cities. In this paper, we propose the use of these maps in order to be applied as a teaching methodology with a dual purpose; on the one hand, for learning about cartographic design and, on the other hand, as a tool for understanding the territory through cognitive maps.